Silicon phase origin on glassy carbon in KF-KCl-K2SiF6 fusion - S. I. Zhuk; L. M. Minchenko; O. V. Chemezov; V. B. Malkov; A. V. Isakov; Yu. P. Zaikov (Chimica Techno Acta)
Silicon nucleation process was invesigated in melt KF-KCl-K2SiF6 on glassy carbon substrates at 675 ºС by chronoamperometric method. Using data of the chronoamperograms the linear dependence I – τ3/2 was constructed. That fact testified the progressive nucleation mode of silicon. As seem from SEM micrographs silicon crystals obtained by a single pulse had different sizes, that also confirmed the progressive nucletion mode.